Evacuation Experiment Study in Up and Down Escape Staircase of Underground Road - Da-jun Yuan; Hui Jin; Zhi-cong Chen; Sheng-nan Liu (Advances in Civil Engineering)
To measure evacuation basic parameters, reveal evacuation performance, and study reasonable staircase spacing of up and down escape staircase in case of fire, an evacuation experiment, which was based on the most unfavorable evacuation scenario, was conducted. The experiment took personnel and vehicles of actual underground road traffic into account, and evacuation process image data were extracted and analyzed by artificial statistics. Experimental results indicate that the personnel plane evacuation speed is between 1.43 and 1.95 m/s, and the upstairs evacuation speed that is less affected by gender and age is mainly between 0.5 and 1.1 m/s; under the escape stairs width of 0.8 m, the average capacity of escape staircase is 0.7 P/s, and the entrance of the staircase is evacuation bottleneck and queuing phenomenon occurs. Based on the experiment, a calculation model of three-phase personnel net evacuation time was established. By simplifying the evacuation model, a calculation formula of the reasonable escape stair spacing considering the influence of multiple factors was proposed. And the proposed theoretical model was verified by project cases of up and down escape staircase. With 2 min emergency broadcasting time and 6 min Available Safety Evacuation Time of medium-sized fire as the Personnel Safety Evacuation Rule’s reference, the recommended value of escape staircase spacing of single pipe double-deck two-way four-lane (double pipes double-deck two-way eight-lane) underground roads is 64.3 m.